1989
DOI: 10.3109/02656738909140466
|View full text |Cite
|
Sign up to set email alerts
|

Re-induction of hsp70 synthesis: An assay for thermotolerance

Abstract: Of the many heat shock proteins (HSPs), hsp70 appears to correlate best with heat resistance, either permanent or transient. We have investigated various approaches to quantify the concentration of hsp 70, and examined the relationship between hsp70 and cells' thermal sensitivity during the development and decay of thermotolerance in model systems. Here, experiments were performed to determine the possibility of using the rate of synthesis of hsp70 after a second test heat shock to predict the kinetics of ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…However, the increased level of HSP 70 protein after heat shock was similar to results obtained by Auffray et al, (1995) and Juneja et al, (1998). This is because the loss of normal cellular functions due to sudden temperature increase is recovered by the synthesis of stress proteins such as Hsps (Juneja et al, 1998;Li and Mak, 1989;Urban-Chmiel et al, 2013).…”
Section: Levels Of Heat Shock Protein Synthesissupporting
confidence: 64%
“…However, the increased level of HSP 70 protein after heat shock was similar to results obtained by Auffray et al, (1995) and Juneja et al, (1998). This is because the loss of normal cellular functions due to sudden temperature increase is recovered by the synthesis of stress proteins such as Hsps (Juneja et al, 1998;Li and Mak, 1989;Urban-Chmiel et al, 2013).…”
Section: Levels Of Heat Shock Protein Synthesissupporting
confidence: 64%
“…Role of protein (HSP) synthesis in thermotolerance Levels of HSP70 (Laszlo and Li, 1985;Li, 1985;Laszlo, 1988a;Li and Mak, 1989), and more recently also HSP27 (Chretien and Landry, 1988;Landry et al, 19891, were shown to correlate fairly well with the development and decay of thermotolerance as well as with the heat sensitivity of various (resistant) cell lines. Also, a role for HSP90 in thermotolerance has been suggested (see Lindquist and Craig, 1988 for review).…”
Section: Resultsmentioning
confidence: 99%
“…Particularly good correlations were reported for heat tolerance and cellular HSP70 levels (Laszlo and Li, 1985;Laszlo, 1988b;Li and Mak, 1989;Li et al, 1991) and, more recently, HSP27 levels (Chretien and Landry, 1988;Landry et al, 1989). However, inhibition of protein (and HSP) synthesis during TT development by cycloheximide (CHX), did not always (totally) inhibit the expression of thermotolerance at the survival level.…”
mentioning
confidence: 99%
See 2 more Smart Citations